UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL BAWANG DAYAK (Eleutherine polmifolia (L.) Merr) TERHADAP Salmonella typhi dan Escherichia coli - Nofita; Selvi Marcellia; Ade Untari (JFL : Jurnal Farmasi Lampung, 2021)
Dayak onion (Eleutherine polmifolia (L.) Merr) was a typical plant of Kalimantan. Empirically dayak onion (Eleutherine polmifolia (L.) Merr) used by the comunity to treat skin infections. The purpose of this study was to determine the antibacterial activity of ethanol extract of dayak onion power against Salmonella typhi and Escherichia coli bacteria. The highest concentration used was 100%, and the lowest concentration was 0,5%. As a control of cloramfenikol for Salmonella typhi and ciprofloxacin for Escherichia coli bacteria. This research method used agar diffusion. The results showed the ethanol extract of dayak onion (Eleutherine polmifolia (L.) Merr) contained flavonoids, alkaloids, tannins and phenols with the highest levels was by tannins at 7,45%. Dayak onion (Eleutherine polmifolia (L.) Merr) are inhibiting the growth of Salmonella typhi bacteria at a minimum inhibitory concentration (MIC)of 1% with a inhibition zone diameter of 6,24 mm and 0,9% with a inhibition zone diameter of 6,20 mm at Escherichia coli bacteria.Keywords : Eleutherine polmifolia (L.) Merr, Salmonella typhi, Escherichia coli, Agar diffusion, MIC